ESG PRINCIPLES, SUSTAINABLE FINANCE, AND DIGITAL TRANSFORMATION IN THE MODERN FINANCIAL SECTOR - Nematillayeva Nargiza Shoxidaliyevna; Khusanov Salokhiddin (TADQIQOTLAR, 2026)
Abstract Environmental, Social, and Governance (ESG) principles have become one of the most influential frameworks in modern corporate governance, sustainable finance, and investment management. ESG standards are increasingly used to evaluate corporate responsibility, ethical management, environmental sustainability, and long- term organizational performance. Financial institutions, governments, investors, and international organizations actively integrate ESG principles into strategic planning, investment analysis, and regulatory systems. The purpose of this article is to analyze the role of ESG in the financial sector, examine the relationship between ESG and digital transformation, and evaluate the opportunities and challenges associated with sustainable finance. The study explores the three pillars of ESG, the development of ESG investing, the impact of artificial intelligence and financial technologies on sustainability management, international ESG standards, and future trends shaping responsible finance. The article concludes that ESG integration significantly contributes to financial stability, transparency, innovation, and sustainable economic development.